Implementing Multiple Intellegence Approach To Improve The Speaking Ability of The Eight Grade Students of SMP Negeri 3 Duampanua - Muliani; Ammang Latifa; Rafi'ah Nur (La Parole : Journal of Language Teaching and Pedagogy, 2019)
The major problems of this research were how to enhance the students’ speaking ability. Then how to motivate the students to speak in English so this research conducted to find out whether implementing Multiple Intelligence effective to improve the students’ speaking of SMP Negeri 3 Duampanua. A quasi-experimental method was carried out by researcher in this research. The population was the eight grade students of SMP Negeri 3 Duampanua. VIII.1 and VIII.2 were taken as sample which consists of 25 students for each class VIII.1 was chosen as the experimntal class, while VIII.2 was chosen as the control class. The instruments that used in collecting the data were interview test and questionnaire. The procedure in collecting data were divided into 3 stages namely pre-test, treatment, and post-test. The data obtained through the test were analyzed quantitatively and qualitatively. The result of the research shows the students’ speaking ability of the experimental was better than the control group. It was proved by the data of the students’ mean score on experimental class was higher tha the control group (69.16 ˃ 60.52). Futhermore, implementing multiple intelligence improve the student speaking ability. Besides, the research finding also shows the students interest toward the implementing of this simulation. It was proved by the data from questionnaire that the students’ interest was which categorized as strongly agree.